2022
DOI: 10.1177/17562864221123195
|View full text |Cite
|
Sign up to set email alerts
|

Effect of early integrated robot-assisted gait training on motor and balance in patients with acute ischemic stroke: a single-blinded randomized controlled trial

Abstract: Background: Gait disruption is a common poststroke problem. Robot-assisted gait training (RAGT) might improve motor function, balance, and activities of daily living. Objective: We compared the clinical effectiveness of early integrated RAGT using the Walkbot robotic gym with an intensity-matched enhanced lower limb therapy (ELLT) program and with conventional rehabilitation therapy (CRT) in patients with acute ischemic stroke. Methods: A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 34 publications
(39 reference statements)
0
25
0
Order By: Relevance
“…Previous studies started training 22.0–25.9 days after the onset of stroke, whereas the start of training was 7.9 days after stroke onset in the current study. Previous studies examining the efficacy of RAGT from the early phase after stroke onset reported that the time required to achieve beneficial results was shortened by early RAGT 17–20 . Therefore, we believe that early Welwalk training was no less efficient for inducing gait improvement compared with starting training in the subacute phase and shortened the time required to regain gait independence.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Previous studies started training 22.0–25.9 days after the onset of stroke, whereas the start of training was 7.9 days after stroke onset in the current study. Previous studies examining the efficacy of RAGT from the early phase after stroke onset reported that the time required to achieve beneficial results was shortened by early RAGT 17–20 . Therefore, we believe that early Welwalk training was no less efficient for inducing gait improvement compared with starting training in the subacute phase and shortened the time required to regain gait independence.…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies examining the efficacy of RAGT from the early phase after stroke onset reported that the time required to achieve beneficial results was shortened by early RAGT. [17][18][19][20] Therefore, we believe that early Welwalk training was no less efficient for inducing gait improvement compared with starting training in the subacute phase and shortened the time required to regain gait independence. However, because this study did not have a control group and used different robotic devices than those used in previous studies, [17][18][19][20] this conclusion cannot be drawn conclusively from the current results.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A total of 13 interventional studies reported data on quality of life/physical health quality of life for both interventional and control groups. 12,15,17,34,41,54 Pooling these studies, intervention using an exoskeleton appeared to improve the quality of life/physical health quality of life of participants (adjusted Hedges’g 0.58, 95% CI 0.28, 0.88; Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Recent work, including reviews and meta-analyses of a moderate body of previous work also suggests but does not clearly indicate differential benefits of robotic training for patients in the acute and subacute phases of stroke [ 21 , 29 32 ]. There appears to be more support for robotic therapy assisting non-ambulatory acute stroke patients [ 21 , 32 , 33 ] or generally more impaired patients [ 34 , 35 ] or favoring acute/sub-acute as opposed to chronic stroke patients [ 30 , 31 , 36 ] although limited evidence exists that higher functioning ambulatory patients can benefit [ 8 ]. Our results add evidence to further the idea that robotic based training is helpful earlier post-stroke but even for patients who are ambulatory at baseline.…”
Section: Discussionmentioning
confidence: 99%